2020
DOI: 10.3390/jcm9113627
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Elevated Copeptin and High-Sensitivity Cardiac Troponin T in Patients with and without Acute Coronary Syndrome: The ConTrACS Study

Abstract: Aims: We aimed to assess the prognostic role of copeptin in patients presenting to the emergency department with acute symptoms and increased high-sensitivity cardiac troponin T. Methods: A total of 3890 patients presenting with acute symptoms to the emergency department of Heidelberg University Hospital were assessed for increased hs-cTnT (>14 ng/L) from three cohorts: the Heidelberg Acute Coronary Syndrome (ACS) Registry (n = 2477), the BIOPS Registry (n = 320), and the ACS OMICS Registry (n = 1093). In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…However, we should also consider that the C-statistics of 0.718 for the combination of increased hs-cTnI and copeptin is rather modest and hence has to be interpreted within the context of the individual clinical situation. This observation in patients with confirmed COVID-19 is very consistent with findings in 3890 patients presenting with acute symptoms to the emergency department [ 24 ]. In a multivariate Cox regression model, elevated copeptin was independently associated with all-cause death in the acute coronary syndrome (HR = 1.7 (95% CI 1.3–2.3), p = 0.002) and non—acute coronary syndrome cohort (HR = 2.7 (95% CI 1.4–5.0), p = 0.0018).…”
Section: Discussionsupporting
confidence: 89%
“…However, we should also consider that the C-statistics of 0.718 for the combination of increased hs-cTnI and copeptin is rather modest and hence has to be interpreted within the context of the individual clinical situation. This observation in patients with confirmed COVID-19 is very consistent with findings in 3890 patients presenting with acute symptoms to the emergency department [ 24 ]. In a multivariate Cox regression model, elevated copeptin was independently associated with all-cause death in the acute coronary syndrome (HR = 1.7 (95% CI 1.3–2.3), p = 0.002) and non—acute coronary syndrome cohort (HR = 2.7 (95% CI 1.4–5.0), p = 0.0018).…”
Section: Discussionsupporting
confidence: 89%
“…A risk stratification, an important issue in this context, 37,38 yielded the following results. Levels above 100 ng/L of cTnT indicate high risk with very high mortality rates.…”
Section: Discussionmentioning
confidence: 97%
“…However, the role of copeptin in the prognosis is less validated and has not been recommended. Several studies have indicated that copeptin is a useful prognostic predictor for adverse outcomes in patients with ACS (83,(161)(162)(163)(164), and the predictive performance for 180-day mortality was significantly better in combination with copeptin and cTnI than with cTnI alone (75). However, some controversial results have argued that there is no significant predictive ability of copeptin (alone or with cTn) for ACS outcomes (108,165,166).…”
Section: Copeptin To Predicting Mortality and Adverse Outcome In Amimentioning
confidence: 99%